Systematic Literature Review on Human Resource Management Effect on Organization Performance - Shashi Kant; Metasebia Adula; Zerihun Ayenew Birbirsa (Pelopor Publikasi Akademika, 2022)
Present study is a result of a systematic review of literature on human resource management functionalism in the sphere of Organizational performance. It investigates different problems associated with human resource management in predicament organizations under such situation and explores the role of human resource management. The theoretical reinforcements are done through a systematic review and subsequent thematic content analysis of literature like published research papers, along with reports from published literature; these were critically examined and best matching documents are strategically selected for inclusion to reach conclusion. The outcome highlights the need for human resource management mangers to adopt innovative techniques for faculty and staff empowerment to navigate through the rapidly changing scenario and do the best on the constrained background. A conceptual qualitative framework is developed and prescribed for functionalism of customized human resource management to engross stakeholders in amicably avoiding recalcitrance. This framework can assist human resource management mangers to identify the opportunities during this crisis and make meaningful decisions to solve problems and build a supportive culture. This framework can assist an educational leader to manage stakeholders’ expectations through mutual collaboration in working towards overcoming anticipated obstacles and add value to both academicians and practitioners.